PSXII-22 Factors Influencing Youth Horse Industry Involvement: A Survey of Youth Participants. (7th December 2018) - Rhyne, J; Spooner, H; Herrin, A; Jousan, D
Abstract: Participation numbers in most youth horse industry breed and discipline groups have declined in recent years. Speculation to the cause of such includes the economic downturn, an increase in youth involvement in other activities, and increased time spent on academics. This study was designed to investigate factors influencing youth industry involvement by surveying youth participants across a multitude of industry groups. The survey also sought to determine the youths' desire to maintain industry involvement in college and beyond. The internet-based survey recorded 1730 responses from U.S. youth age 14–18 during a two-month period in 2017. Eighteen industry groups were represented, with 700 participants (45.9%) involved in 4-H and 490 (32.1%) involved in the United States Equestrian Federation as the largest represented populations. Ninety-one percent of participants competed in horse shows or other competitive events, identifying location of shows, ability to be competitive in these shows, and friends involved as the main reasons for selecting the group/discipline of their choice. Nearly 77% of participants reported taking lessons with an instructor.Ninety-four percent of participants indicated a desire to be more involved in horse activities. Sixty-three percent reported involvement in other activities, including other sports and academic clubs; with the majority suggesting those activities occupy 2–5 hours per week. When asked the most limiting factor to their involvement, 36% indicated family finances, while 28% indicated time spent on academics. There was no influence of organization on factors influencing involvement (p=0.36). Sixty-four percent agreed or strongly agreed to a desire to pursue a career in the horse industry, while 94% indicated a desire to remain active in the horse industry beyond college. The results of this survey suggest a high level of involvement by currently engaged youth and a desire to remain active in the horse industry in college and beyond.